Per Enzo. Studi in memoria di Vincenzo Matera - Ciaralli, Antonio; CAPO, Lidia (Reti Medievali E-Book, 2015)
The miscellanea collects fifteen essays, which are arranged over the chronological span of the entire Middle Ages and the early modern age, and dedicated to issues of archaeological, documentary, codicological, economic, numismatic and social interest: a variety reflecting, albeit partially, the culture, interests and humanity which belonged to Vincenzo Matera.